La cadena de custodia en el proceso penal ecuatoriano - Manosalvas, Cynthia G. (2019)
The main objective of this investigation was to analyze the omission or non-compliance of the chain of custody in the Ecuadorian criminal process, and as specific objectives, the legal analysis of the institution of the chain of custody, the study of the probation regime in the law Ecuadorian criminal procedure and finally, in scope of noncompliance with the chain of custody in the Ecuadorian criminal process. The investigation had a qualitative approach and is descriptive, also focused on an in-depth analysis of the chain of custody and the extent of non-compliance with the chain of custody in the Ecuadorian criminal process, a critical interpretation of the analyzed institution was made, according to the documentary analysis of doctrine, regulations and jurisprudence. Concluding that there is a need that failure to comply with the chain of custody does not imply the inadmissibility of the evidence, but that the valuation is affected, since the inadmission proceeds due to other circumstances and pursues another nature.